The non-constant-sum Colonel Blotto game - Brian Roberson; Dmitriy Kvasov (Center for Economic Studies and ifo Institute (CESifo), 2008)
The Colonel Blotto game is a two-player constant-sum game in which each player simultaneously distributes her fixed level of resources across a set of contests. In the traditional formulation of the Colonel Blotto game, the players' resources are use it or lose it in the sense that any resources which are not allocated to one of the contests are forfeited. This paper examines a non-constant-sum version of the Colonel Blotto game which relaxes this use it or lose it feature. We find that if the level of asymmetry between the players' budgets is below a threshold, then the unique set of equilibrium univariate marginal distributions of the non-constant-sum game is equivalent up to an affine transformation to the unique set of equilibrium univariate marginal distributions of the constant-sum game. Once the asymmetry of the players' budgets exceeds the threshold we construct a new equilibrium.
Keywords: C7; 330; Colonel Blotto game; all-pay auction; contests; Spieltheorie; Auktionstheorie; Wettbewerb; Theorie